ANSWER
![x ^{2} = - 4(y - 1).](https://tex.z-dn.net/?f=x%20%5E%7B2%7D%20%20%3D%20%20-%204%28y%20-%201%29.)
EXPLANATION
Since the parabola has the (0, 0) and the directrix at y=2.
The equation is of the form
![{(x - h)}^{2} = - 4p(y - k)](https://tex.z-dn.net/?f=%20%7B%28x%20-%20h%29%7D%5E%7B2%7D%20%20%3D%20%20-%204p%28y%20-%20k%29)
where (h,k) is the vertex.
The vertex is half way between the directrix and the focus.
The vertex will be at (0,1)
and is the distance from the vertex to the focus which is 1.
![{(x - 0)}^{2} = - 4(1)(y - 1)](https://tex.z-dn.net/?f=%7B%28x%20-%200%29%7D%5E%7B2%7D%20%20%3D%20%20-%204%281%29%28y%20-%201%29)
![x ^{2} = - 4(y - 1)](https://tex.z-dn.net/?f=x%20%5E%7B2%7D%20%20%3D%20%20-%204%28y%20-%201%29)
Answer:
y=4.5
Step-by-step explanation:
2y+3=11
2y=11-3
2y=9
y= 4.5
Simplify both sides of the equation
x/16−(x+2/8) = 2x/16 + −1/8x + −1/4 = 2
Distribute
1/16x + −1/8x + −1/4 = 2
(1/16x + −1/8x)+(−1/4) = 2
Combine Like Terms
−1/16x + −1/4 = 2
Add 1/4 to both sides.
−1/16x + −1/4 + 1/4 = 2 + 1/4
−1/16x = 9/4
Multiply both sides by 16/(-1).
(16/−1)*(−1/16x)=(16/−1)*(9/4)
x=−36
Answer:
its 3
Step-by-step explanation:
Simplifying
8 = 3x + -1
Reorder the terms:
8 = -1 + 3x
Solving
8 = -1 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
8 + -3x = -1 + 3x + -3x
Combine like terms: 3x + -3x = 0
8 + -3x = -1 + 0
8 + -3x = -1
Add '-8' to each side of the equation.
8 + -8 + -3x = -1 + -8
Combine like terms: 8 + -8 = 0
0 + -3x = -1 + -8
-3x = -1 + -8
Combine like terms: -1 + -8 = -9
-3x = -9
Divide each side by '-3'.
x = 3
Simplifying
x = 3 this took forever to type hope it helped
Answer:
can you show us the table?
Step-by-step explanation: